Science is the Basis for a Country’s Modernization - Vasyliev, Oleksandr (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The development of sciences and high technologies is the most real way for a country to occupy a worthy place among developed states. The level of national sciences to a great extent determines the fundamental basics of economical and military security of a state. The modern condition and transformation of Russian scientific and technological complex tendencies show that the country will not be able to become a leader of global and regional integrations